Digital Economy, Consumption Upgrading and Domestic Demand Level: An Empirical Analysis of PVAR Based on Provincial Panel Data - Jianhong Fan; Jiaxuan Zhang; Huichao Wu; Chen Liang (SAGE Open)
This study selects provincial panel data from 2008 to 2019 and constructs a panel vector autoregressive (PVAR) model to explore the bidirectional interactive relationship between digital economy, consumption upgrading and domestic demand level through the Granger causality test, the analysis of impulse response function and variance decomposition. Firstly, the GMM estimation results show that there is a significant bidirectional interactive effect between digital economy and domestic demand level, and a significant bidirectional interactive effect between digital economy and consumption upgrading, while the interactive effect between consumption upgrading and domestic demand level is weak. Secondly, the analysis of impulse response function shows that domestic demand level can sustainably promote the development of digital economy, and the promotion effect of digital economy on domestic demand level is immediate. However, in the long run, digital economy has a gradually weakening hindering effect on domestic demand level. Digital economy and consumption upgrading show a “V-shaped” relationship. The shackles of mutual promotion between consumption structure and scale still exist. Thirdly, the analysis of variance decomposition shows that the mutual contribution rate of digital economy and domestic demand level is low, the mutual contribution rate of digital economy and consumption upgrading is high, and the mutual contribution rate of consumption upgrading and domestic demand level is low. The implications in this study can help drive digital economy development, promote consumption upgrading and raise domestic demand level.